Bank noninterest income and risk: An empirical analysis of commercial banks in Malaysia - Chan, De Long (2016)
The purpose of this study is to investigate the impact of noninterest income on Malaysian commercial banks risk for over the period 2005 to 2014. Previous studies document that noninterest income activities may influence bank risk as the earnings volatility increases when banks expand into noninterest income generating activities due to higher level of competition. Employing a sample of 27 commercial banks in Malaysia, the finding of this study suggests that banks' risk will increase when net noninterest income increase. This study also includes bank size and return on equity (ROE) as control variables to see their impact on bank risk. The results indicate that larger banks tend to have lower risk, while banks with higher ROE will also have lower risk